Penguasaan Keahlian Akuntansi, Pajak, Software Akuntansi Dan Bahasa Inggris Terhadap Kepercayaan Diri Mampu Bersaing Dalam Dunia Kerja (Studi Pada Mahasiswa Akuntansi ITB Ahmad Dahlan Jakarta) - Eko Hadi Siswanto; Nurwati Nurwati (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2019)
The purpose of this research is to study it there is positive influence of expertise of mastery accounting,taxation,accounting software and english language toward confidence being able to compete workplace. The research method used is causal, with the unit of analysis the accounting student . Sampling method used stratified random sampling. The mastery accounting expertise,tax,accounting software and english language toward confidence being able to compete workplace by using the instruments measured questionnaire with likert scale. Source analysis performed by descriptive analysis and linear regression. The result shows that’s influence of mastery accounting expertise,tax,accounting software and english language toward confidence being able to compete workplace with determination coefficient is 12,18%.